Acute responsiveness to single leg cycling in adults with obesity. Issue 24 (21st December 2022) - Gries, Kevin J.; Hart, Corey R.; Kunz, Hawley E.; Ryan, Zachary; Zhang, Xiaoyan; Parvizi, Mojtaba; Liu, Yuanhang; Dasari, Surendra; Lanza, Ian R.
Abstract: Obesity is associated with several skeletal muscle impairments which can be improved through an aerobic exercise prescription. The possibility that exercise responsiveness is diminished in people with obesity has been suggested but not well‐studied. The purpose of this study was to investigate how obesity influences acute exercise responsiveness in skeletal muscle and circulating amino metabolites. Non‐obese (NO; n  = 19; 10F/9M; BMI = 25.1 ± 2.8 kg/m 2 ) and Obese (O; n  = 21; 14F/7M; BMI = 37.3 ± 4.6 kg/m 2 ) adults performed 30 min of single‐leg cycling at 70% of VO2 peak. 13 C6 ‐Phenylalanine was administered intravenously for muscle protein synthesis measurements. Serial muscle biopsies (vastus lateralis) were collected before exercise and 3.5‐ and 6.5‐h post‐exercise to measure protein synthesis and gene expression. Targeted plasma metabolomics was used to quantitate amino metabolites before and 30 and 90 min after exercise. The exercise‐induced fold change in mixed muscle protein synthesis trended ( p  = 0.058) higher in NO (1.28 ± 0.54‐fold) compared to O (0.95 ± 0.42‐fold) and was inversely related to BMI (R 2  = 0.140, p  = 0.027). RNA sequencing revealed 331 and 280 genes that were differentially expressed after exercise in NO and O, respectively. Gene set enrichment analysis showed O had six blunted pathways related to metabolism, cell to cell communication, and protein turnover after exercise. The circulating amine response further highlighted dysregulations related to protein synthesis and metabolism in adults with obesity at the basal state and in response to the exercise bout. Collectively, these data highlight several unique pathways in individuals with obesity that resulted in a modestly blunted exercise response. Abstract :